2021
DOI: 10.1016/j.isci.2021.102783
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation reverts mouse epiblast stem cells to naive state

Abstract: Despite increasing knowledge on primed and naive pluripotency, the cell signaling that regulates the pluripotency type in stem cells remains not fully understood. Here we show that AMP kinase (AMPK) activators can induce the reversion of primed mouse epiblast stem cells (mEpiSCs) to the naive pluripotent state. The addition of AMPK activators alone or together with leukemia inhibitory factor to primed mEpiSCs induced the appearance of naive-like cells. After passaging in naive culture conditions, the colony mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…We have previously reported that p38 is a critical downstream of AMPK in the maintenance and induction of the naïve state of mouse PSCs (Liu et al, 2019; Liu et al, 2021). Then, we examined the involvement of p38 in the AICAR-elicited naïve conversion of human PSCs.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We have previously reported that p38 is a critical downstream of AMPK in the maintenance and induction of the naïve state of mouse PSCs (Liu et al, 2019; Liu et al, 2021). Then, we examined the involvement of p38 in the AICAR-elicited naïve conversion of human PSCs.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, We have reported that the treatment with AICAR or the expression of a constitutive active form of p38 (CA-p38) can maintain the naïve state of mouse ESCs and convert mouse EpiSC to naïve mouse ESCs (Liu et al, 2019; Liu et al, 2021). Based on these data, we examined whether the treatment with AICAR or CA-p38 could convert primed human PSCs to the naïve state.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations